2020
DOI: 10.1177/0748233720922722
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress status of Turkish welders

Abstract: Welding, a fabrication process that joins metals or thermoplastics by causing coalescence, is indispensable in modern society and ubiquitous in industry. Welding generates fumes that contain several metals and gases that comprise fine and ultrafine particles with the potential for adverse effects. Although health risks of welders have been evaluated in different populations, occupational exposure to welding fumes is still considered to be an important health problem, especially in developing countries. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The results showed that these three black soybean peptides we screened out could alleviate the abnormal production of Pb-induced ROS and restore cells to a certain extent. Guo et al have shown that Pb 2+ -induced damage propagates through an intercellular junction communication (GJIC) between PC12 cells while inducing apoptosis in bystander cells through ROS mitochondrial-dependent apoptosis signals [ 23 ]. Yuan et al said SOD and GSH/GSSG quickly cleared the ROS within cells to keep the stability of the internal structures of the cells and tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that these three black soybean peptides we screened out could alleviate the abnormal production of Pb-induced ROS and restore cells to a certain extent. Guo et al have shown that Pb 2+ -induced damage propagates through an intercellular junction communication (GJIC) between PC12 cells while inducing apoptosis in bystander cells through ROS mitochondrial-dependent apoptosis signals [ 23 ]. Yuan et al said SOD and GSH/GSSG quickly cleared the ROS within cells to keep the stability of the internal structures of the cells and tissue.…”
Section: Resultsmentioning
confidence: 99%
“…It is also a basic electron donor for GPx enzymes. GR is a flavin protein whose function is to catalyze NADPH-dependent reduction of GSSG to GSH, which is necessary to maintain adequate cellular GSH contents [ 23 ]. GSH-Px can catalyze glutathione from decreased GSH to oxidized GSSG, and GSH consumption and GSSG production reflect the degree of intracellular oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Turkish study on the correlation between serum metal levels and oxidative stress biomarkers among welders identified a clear positive link between 8-OHdG levels and serum Cr, Mn, Cu, and Pb levels (Tokaç et al, 2020).…”
Section: Aminian Et Al (2019) Frommentioning
confidence: 99%
“…When taken in large quantities, the copper shows toxic properties for metabolism. The most common of these is oxidative stress and a neurodegenerative Wilson's disease [24], [25]. In this respect, determining the amount of copper in domestic water has been essential.…”
Section: Introductionmentioning
confidence: 99%